Development of Fable-Based Indonesian Language Learning Materials as A Media for Developing the Character of Elementary School Students - Friendha Yuanta; Suprihatien Suprihatien (IKIP PGRI Bojonegoro, 2026)
Indonesian language is one of the subjects at the elementary level. School Basic. Indonesian language subjects consist of skills listening, speaking, reading, and writing skills. speak can be taught to students in various teaching methods. One of them is using teaching materials so that students can learn in a fun way. The development of teaching materials for Indonesian language subjects based on Fables in grade 4 aims to determine the feasibility and effectiveness of learning media to build student character and increase students' interest in understanding fable stories. The model of this study is to use the ADDIE model which through the use of puppets with animal characters based on fables, students can more easily understand the theme, morals, and characters in the story. The results of the application of this media show an increase in students' active participation, understanding of the story, and their ability to retell fable stories and character building of students. This type of research is research and development in the form of developing learning media in the form of puppet media with animal characters based on fables that are effective for the learning process. The level of media feasibility is set at 90% based on expert test analysis, the suitability of teaching materials is set at 88.33%, and 91.48% based on the survey student Which agree to use media puppet with figure animal based on fable for the learning process teach.